(untitled) (Albayan Scientific Journal, 2023)
This study was carried out to determine and to estimate the diversity and the biomass of sub-tropical trees in 50 study plots at Ashaavieen Nature Reserve, Msallata, Libya. The total number of trees recorded was 1024 from 7 species of 6 families which are; Anacardiaceae, Caesalpiniaceae, Mimosaceae, Oleaceae, Rhamnaceae, and Pinaceae. Pinus halepensis was the most dominant species with an Importance Value Index (IVI) of 54.20%. The total basal area (BA) recorded was at 7.33 m²/ha with Pinus halepensis representing the highest value at 6.21 m²/ha (84.72%). Shannon-Wiener Diversity Index (H’) calculations have indicated low biodiversity in all study plots (H’ > 1.5). Total biomass estimation was at 8483.61 t/ha with Pinus halepensis and Pistacia lentiscus contributions to the highest values respectively.